Vibration damping of Ni-Mn-Ga/silicone composites. (15th March 2018) - Feuchtwanger, J.; Seif, E.; Sratongon, P.; Hosoda, H.; Chernenko, V.A.
Abstract: Ferromagnetic shape memory alloy (FSMA)/polymer composites are promising materials for mechanical vibration damping. One of the main issues is that mechanically active FSMA particles from different types of viable sources for large quantities of these particles have not been compared under the same conditions. In this paper we compare the dynamic mechanical response of NiMnGa/silicone composites, made of different types of mechanically active particles, using the same matrix and experimental conditions. The study reveals a strong influence of both volume fraction of FSMA in the composite and morphology of the particles used as fillers on the vibration damping of composites. Graphical abstract: Image 1